PEMANFAATAN TANAMAN DAUN PAKCOY (Brassica rapa sups. Chinensis) UNTUK MEMBANTU MENURUNKAN KADAR KOLESTEROL - Purnama Aji, Nurwani; Devi Novia; Silta Monica; Vhebie armandha fhunkie; Anjasuma bijaksana; Enjelsi Efriadin Safitri; Yega Anggela; Cindy Aulia (Jurnal Pengabdian, 2023)
Pakcoy leaves (Brassica rapa subsp. Chinensis) are one of the plants that can reduce cholesterol levels with their chemical content of flavonoids, saponins, and tannins. This activity aims to promote public health regarding the use of pakcoy leaves (Brassica rapa subsp. Chinensis) in helping to reduce cholesterol levels and provide information on how to obtain pakcoy leaf extract simply by the infudation method. This promotional activity was carried out in collaboration with students and teachers of SMAN. 09 Bengkulu City. This activity is carried out by means of counselling by providing material on how the use of pakcoy leaf plants can help reduce cholesterol levels with simple materials and methods, namely using the infudation method. The results of the implementation activities that we did on Wednesday, June 14, 2023, with students at SMA Negeri 9 Bengkulu City began to show the benefits of pakcoy leaf plants. From the initial counselling, students did not know the benefits of pakcoy leaves to help reduce cholesterol levels. Then, after counselling, students already knew the benefits of pakcoy leaves.